Preliminary evaluation of a novel Aboriginal community–controlled prison health service for First Nations people - Shehara Arumugam; Julie Tongs; Ana Herceg (Australian and New Zealand Journal of Public Health)
Objective: This study aimed to provide a preliminary evaluation of the Winnunga Nimmityjah Health and Wellbeing Service which commenced operations at the Australian Capital Territory's adult prison in 2019. Methods: A mixed-method approach was utilised to evaluate the service from 1 January 2019 to 31 December 2020. The quantitative arm described health status and health care engagement of enrolled detainees, and included a comparison of preventative health measures with the Winnunga community-based service. A qualitative arm involved focussed, semi-structured interviews with Winnunga staff members who worked at the prison service. Results: There were 61 detainees enrolled (from 168 requests for enrolment), with 92% identifying as Aboriginal and/or Torres Strait Islander. Health needs among detainees were skewed towards mental illness and substance use. The provision of primary and preventative health care was comparable to or better than the community-based service. Qualitative analysis of staff interviews identified four themes: provision of holistic and community-led care, workforce constraints, access to opioid agonist treatment and challenges working within a correctional facility. Conclusions: Winnunga was the first Aboriginal Community Controlled Health Organisation to deliver holistic health care to First Nations people in an Australian prison. This evaluation highlights the service’s achievements and provides recommendations for improvement and expansion. Implications for public health: Aboriginal community-controlled organisations can provide high quality, culturally safe health and wellbeing services for First Nations people in prison. The findings of this study provide evidence for the development of similar services in other jurisdictions.